Effectiveness of PNF Pattern in Regular Physical Therapy Sessions on Functional Mobility in Frozen Shoulder : PNF Pattern in Frozen Shoulder Therapy - Ghias, Sidra; Burki, Subhan ur Rehman; Saeed, Hina; Ahmed, Mansoor; Faisal, Muhammad; Solangi, Tariq Ahmed; Asim, Hafiz Ali Bin; Arshad, Sameen; Ahmad, Jawad (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2024)
Frozen shoulder, or adhesive capsulitis, is a musculoskeletal condition that presents with symptoms such as discomfort, nocturnal pain, and limited range of motion. Abduction and external rotation are significantly reduced. Objective: To investigate the effectiveness of combining proprioceptive neuromuscular facilitation (PNF) patterns into routine physical therapy sessions for patients with frozen shoulder. Methods: A six-week quasi-experimental study was conducted on a total of 30 participants, divided into group A (n=15) and group B (n = 15), selected from the outpatient department (OPD). Pain, disability, and range of motion were evaluated as outcome measures. The group A received proprioceptive neuromuscular facilitation (PNF) patterns in addition to their usual physical therapy sessions, and group B only received conventional physical therapy sessions. Disabilities of the Arm, Shoulder and Hand (DASH), VAS (Visual Analog Scale) and goniometer were used to assess pain, disability and range of motion (ROM). Data were analyzed using SPSS version 23.0. Results: Both groups showed a significant reduction in DASH and VAS scores and an increase in ROMs, as group A showed a better result in terms of DASH score and abduction range (p<0.05). Conclusions: Both the experimental and control groups had statistically significant outcomes. The PNF pattern and Codman exercises both have a positive impact on rehabilitation. However, PNF is more advanced because it involves a combination of movements that are also useful in daily activities. Additionally, PNF helps develop memory for correct patterned movements. On the other hand, Codman exercises are only effective for retaining and improving shoulder ranges.